2021
DOI: 10.1177/03400352211057145
|View full text |Cite
|
Sign up to set email alerts
|

Automating intellectual freedom: Artificial intelligence, bias, and the information landscape

Abstract: Anxieties over automation and personal freedom are challenging libraries’ role as havens of intellectual freedom. The introduction of artificial intelligence into the resource description process creates an opportunity to reshape the digital information landscape—and loss of trust by library users. Resource description necessarily manipulates a library’s presentation of information, which influences the ways users perceive and interact with that information. Human catalogers inevitably introduce personal and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…As a result, they suggested that organizational factors include technology capability, strategy and roadmap, top management support, digital maturity, reliability, competitive environment, compatibility, relative advantage, cost, external pressure, and organization innovation. Stenberg and Nilsson (2020) and Smith (2022) suggested the following as essential factors: relative advantage, compatibility, and complexity from a technological perspective; top management support, employee capability, and ethics from an organizational perspective; and regulatory environment and competitive pressure from an environmental perspective. Chen et al (2021) viewed AI adoption as significant, considering compatibility, relative advantage, complexity, managerial support, government involvement, and vendor partnership.…”
Section: Ai Technology Adaptation In Network Operationsmentioning
confidence: 99%
“…As a result, they suggested that organizational factors include technology capability, strategy and roadmap, top management support, digital maturity, reliability, competitive environment, compatibility, relative advantage, cost, external pressure, and organization innovation. Stenberg and Nilsson (2020) and Smith (2022) suggested the following as essential factors: relative advantage, compatibility, and complexity from a technological perspective; top management support, employee capability, and ethics from an organizational perspective; and regulatory environment and competitive pressure from an environmental perspective. Chen et al (2021) viewed AI adoption as significant, considering compatibility, relative advantage, complexity, managerial support, government involvement, and vendor partnership.…”
Section: Ai Technology Adaptation In Network Operationsmentioning
confidence: 99%
“…This is often seen as a necessary part of continually improving a system, by providing an algorithm with feedback about its efficacy via data about the user’s behavior when browsing in order to further improve the system. Serious consideration of the dangers to patron privacy should be seen as a crucial element of upholding intellectual freedom with regard to adopting AI technologies in patron-facing services (Smith, 2021).…”
Section: Data Privacymentioning
confidence: 99%
“…Additionally, machine learning algorithms analyse large data sets and make personalized recommendations to patrons. However, the use of AI in libraries also raises some concerns, such as the need for privacy, security and the ethical use of data (Asemi et al, 2020; Panda and Chakravarty, 2022; Smith, 2022). AI is a rapidly evolving field, changing how we interact with technology.…”
Section: Introductionmentioning
confidence: 99%